The Influence of the Collaborative Learning Model with Padlet on Student Learning Motivation in Aqidah Akhlak Learning at the Al-Ma'un Muhammadiyah Baringin Islamic Boarding School: Pengaruh Model Pembelajaran Collaborative Learning dengan Padlet Terhadap Motivasi Belajar Siswa Dalam Pembelajaran Akidah Akhlak Di Pondok Pesantren Al-Ma’un Muhammadiyah Baringin - M.Firly; Siska Yulia Rahmi; Razzaaq fikih al fitra (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This research was motivated by the low learning motivation of students in the Aqidah Akhlak subject at the Al-Ma'un Muhammadiyah Baringin Islamic Boarding School. This low motivation is shown by students' lack of enthusiasm in participating in learning, low active participation, lack of initiative in completing assignments, and the still dominant use of conventional teacher-centered learning models. Therefore, a learning model is needed that is able to increase student involvement, one of which is through the application of the Collaborative Learning model combined with Padlet media. This research aims to determine the effect of the Collaborative Learning learning model with Padlet on students' learning motivation in the Aqidah Akhlak subject. This research uses a quantitative approach with experimental methods. The research was carried out at the Al-Ma'un Muhammadiyah Baringin Islamic Boarding School with research subjects as class VII students on the subject of Disgraceful Morals towards Allah SWT (riya' and nifaq). The independent variable in this research is the Collaborative Learning learning model with Padlet, while the dependent variable is student learning motivation. Data collection was carried out using a learning motivation questionnaire which was prepared based on learning motivation indicators according to Sardiman. Data were analyzed using statistical analysis techniques to test hypotheses regarding the influence of learning models on student learning motivation. It is hoped that the research results will provide an overview of the effectiveness of implementing the Padlet-assisted Collaborative Learning learning model in increasing student learning motivation.